Electron properties investigation of the near-surface region in crystalline semiconductors using the transverse acoustoelectric effect - Tadeusz Pustelny (Archives of Acoustics)
The paper presents the acoustoelectric phenomenon in a layered structure: piezoelectric waveguide – semiconductor. The publication presents an original acoustic method for determining the electrical and electron parameters of the subsurface area in crystalline semiconductors. The method is based on the so-called transverse acoustoelectric effect realized in a layer system: piezoelectric waveguide with Rayleigh surface acoustic wave – semiconductor. The paper discusses the physical foundations of the transverse acoustoelectric effect in the piezoelectric – semiconductor layer system, taking into account the distinctness of the physical properties of the semiconductor near-surface region in relation to its volumetric properties. The work covers many experimental studies of the near-surface region of semiconductors. The original method was presented to determine such surface parameters as: surface potential, surface conductivity, mobility of carriers in the subsurface area, life time of charge carriers in surface states. By means of the acoustic method the following semiconductors have been extensively tested: indium phosphide InP and gallium phosphide GaP. These semiconductors are one of the main semiconductors of group III-V, which are the basis of modern photonics, optoelectronics as well as integrated optics. The work also includes an analysis of the measurement possibilities of the developed acoustic method and its limitations, as well as an analysis of the accuracy of the obtained values of the parameters of the subsurface area of crystalline semiconductors.